DEVELOPMENT OF COMPUTATIONAL THINKING-BASED E-COMIC TO IMPROVE NUMERACY SKILLS STUDENTS - Hanida, Rifa Arma; Maharani, Swasti; Sanusi, Sanusi (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This research is a development research (R&D) motivated by the low numeracy skills of students in understanding data presentation materials. The purpose of the research is to develop learning media in the form of E-Comic based on Computational Thinking (CT) to improve the numeracy skills of seventh grade students. The development model used is ADDIE, which includes five systematic stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of the research were seventh grade students of SMP Negeri 4 Kota Madiun. Data were collected using validation sheet instruments, questionnaires, and tests. The results showed that the E-Comic media obtained validation from media experts with an average percentage of 90%, categorized as very valid. In terms of practicality, this media was considered very practical with an achievement of 89.38% in limited trials and 86.42% in field trials. The effectiveness of the media was analyzed using the N-Gain score, which showed an increase in learning outcomes of 76.18% in limited trials and 77.20% in field trials, both in the high category. The implementation of CT principles in learning through E-Comics has been proven to guide students to think systematically, logically, and creatively in understanding and presenting data. Therefore, this CT-based E-Comic learning medium is valid, practical, effective, and relevant for mathematics learning, particularly data presentation, and is in line with the needs of 21st-century learning.